Studying biological science does not lead to adoption of a healthy lifestyle. (July 2020) - Bhatti, SN; Leidi, A; Leake, D; Li, J-M
Aims: The lifestyle and physical activity (PA) habits of young people play a key role in the prevention of cardiovascular and metabolic diseases at older ages. The current generation of biological science students at university holds promise for better future medicine and medical technology. However, their physical fitness and lifestyle are often ignored. Methods: Lifestyle, PAs and common risk factors for cardiovascular disease before, and at, university were collected from 408 students using self-completed, anonymous surveys between the academic years of 2017 and 2019 from the School of Biological Sciences, University of Reading. Statistical analysis was performed using SAS® 9.4 software. Results: Among the 408 participants, 134 were male and 274 were female with a mean ( SD ) age of 19.6 (2.24). Approximately 19% of participants consumed alcohol beyond the safe limit of <14 units/week (112 g/week). Among them, 65% were males. Before university, 47% of students failed to meet the UK National Physical Activity Guidelines (NPAG) which increased to 56% during university with males exhibiting a steeper incline. Compared to their lifestyles before university, more students had insufficient sleep and displayed greater sedentariness during university. Moreover, 16% of students declared no engagement in PA which was greater than the value of 12% before university. Fitness perceptions worsened by 11% during university particularly for females. Statistical analysis revealed that gender, BMI and fitness perceptions were significantly correlated with PA levels. The most prevalent explanation for inadequacy in meeting NPAG was insufficient time. Conclusions: Compared to their pre-university lifestyles, biological science students at university are more likely to adopt unhealthier behaviours with less time for exercise and prolonged sedentary behaviours, which increases the risk for cardiovascular diseases. It is important to raise awareness of their fitness perceptions and to encourage health-promoting programmes at university.